Harnessing drug/radiation interaction through daily routine practice: Leverage medical and methodological point of view (MORSE 02-17 study) - Vallard, A.; Rancoule, C.; Espenel, S.; Garcia, M.-A.; Langrand-Escure, J.; He, M.Y.; Ben Mrad, M.; El Meddeb Hamrouni, A.; Ouni, S.; Trone, J.-C.; Rehailia-Blanchard, A.; Guillaume, E.; et al. (Radiotherapy and oncology, 2018)
Safety profile of the interaction between anticancer drugs and radiation is a recurrent question. However, there are little data regarding the non-anticancer treatment (NACT)/radiation combinations. The aim of the present study was to investigate concomitant NACTs in patients undergoing radiotherapy in a French comprehensive cancer center. A prospective cross-sectional study was conducted. All cancer patients undergoing a palliative or curative radiotherapy were consecutively screened for six weeks in 2016. Data on NACTs were collected. Out of 214 included patients, a NACT was concomitantly prescribed to 155 patients (72%), with a median number of 5 NACTs per patient (range: 1–12). The most prescribed drugs were anti-hypertensive drugs (101 patients, 47.2%), psychotropic drugs (n = 74, 34.6%), analgesics (n = 78, 36.4%), hypolipidemic drugs (n = 57, 26.6%), proton pump inhibitors (n = 46, 21.5%) and antiplatelet drugs (n = 38, 17.8%). Although 833 different molecules were reported, only 20 possible modifiers of cancer biological pathways (prescribed to 74 patients (34.5%)) were identified. Eight out of the 833 molecules (0.9%), belonging to six drug families, have been investigated in 28 ongoing or published clinical trials in combo with radiotherapy. They were prescribed to 63 patients (29.4%). Drug-radiation interaction remains a subject of major interest, not only for conventional anticancer drugs, but also for NACTs. New trial designs are thus required.